Pengaruh Kepemimpinan Islami Dan Budaya Religiusitas Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Karyawan Sebagai Variabel Intervening Pada PT. Sidogiri Mitra Utama - Kamtari, Gita Ade; Rizal, Mohammad; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This examine goals to decide and examine the impact of Islamic management and religious subculture on employee performance thru task pleasure as an intervening at PT. Sidogiri Mitra Utama. This studies is informal associative research the usage of a quantitative approach. The pattern of this observe used a saturated pattern, particularly eployees of PT. Sidogiri Mitra Utama as many as 73 personnel. gathering facts using a valid and dependable questionnaire. statistics analysis became accomplished the usage of more than one regression linier analysis. The end result of the take a look at found that : 1) Islamic leadership has enormous poor effect on employee overall performance. 2) lifestyle religiosity has a sizeable positive on worker overall performance. 3) Islamic leadership has a great bad impact on process pride. 4) Cultural religiosity has no considerable positive effect on job satisfaction. 6) Islamic management has a significant negative impact on worker performace via task pleasure as an intervening variable. 7) religious culture has a significant poor impact on worker overall performance thru activity satisfactionas an intervening variable. Keywords: Islamic Leadership, Religious Subculture, Worker Performance, And Job Delight.